DICCIONARIO TEOLOGICO DEL ANTIGUO TESTAMENTO - Botterweck, G. Johannes (dirección) (1973)
CONTENIDO: V. 1 FASCICULO 1 (COL. 1-128). -- V. 1 FASCICULO 2 (COL. 129-256). -- V. 1 FASCICULO 3 (COL. 257-384)